PENGARUH PENALARAN MORAL, RETALIASI DAN GENDER TERHADAP KECENDERUNGAN WHISTLEBLOWING INTERNAL - Mesri Welhelmina N. Manafe (Akademi Akuntansi YKPN Yogyakarta, 2015)
Pedoman Sistem Pelaporan Pelanggaran atau Whistleblowing System (WBS) by the Peraturan Komite Nasional Kebijakan Governance (KNKG) is expected to determine whistleblower in Indonesia as one of the form of effective internal controls to prevent fraud and wrong-doing by individuals or corporations. In practice, the regulation is strongly influenced by the individual's intentions. This study uses variable of moral reasoning and retaliate by including gender variables to test its effect on the tendency orintention to do whistleblowing. To answer the research question, this research uses experimental design which is then analyzed using ANOVA for hypothesis testing. Subjects in this study were accounting students UKAW. The results showed that retaliation and moral reasoning affects the tendency of whistleblowing, while gender is not striving against the tendency to blow the whistle. Keywords: Whistleblowing, moral reasoning, retaliation, gender